Employer Branding and Striving in the War of Talent: Exploration Study in the Renewable Energy Sector in the UAE - Al-Zeyoudi, Thani Ahmed (2011)
Anticipations about the shortage of talent and consequent intimidations to companies’ ability to attract and recruit the required employees are threatening the corporations around the globe. The severity of this anxiety is even bigger for the renewable energy industry, due to a huge gap in supply and demand side of alternative energy professionals. The purpose of this paper is explore the employer branding status of a rapidly flourishing renewable energy company in UAE and also to determine that to which extent its strategies have been effective to construct its image as an attractive employer. A mix of quantitative and qualitative techniques is used to analyze the primary data which is collected through open-ended and close ended questionnaires designed for measuring the perceptions of existing and potential employees of the company. The samples of 75 existing employees and 60 potential employees have been used to gain a comprehensive insight into the matter. The key findings of the study include the huge gaps existing in the internally prevailing situation for the company and the general perception in the market about the company as an employer. The areas constituting the setback have also been highlighted, with the particular emphasis on feasible solutions. Considering the discovered veracities, adoption of a thoroughly revised performance appraisal and compensation system, a proactive recruitment strategy and the construction of a healthy psychological contract have been recommended. Furthermore, the elucidation for constituting a flexible career path to make XYZ Company a desirable workplace for generation Y in particular, is also embraced in the recommendations.